Trastornos neuropsiquiátricos asociados al Covid persistente - Díaz S., Mario; Moreira G., Gustavo; Núñez A., Felipe; Ahumada M., Felipe; Durán R., Emilia; Regular S., Antonella; Martínez M., Constanza (Revista Hospital Clínico Universidad de Chile, 2024)
Persistent COVID (PC) is the term used to describe a multisystemic and multifactorial entity, which follows acute SARS-CoV-2 infection. Symptoms must persist for three months or more to define this disorder. The clinical manifestations are variable and nonspecific, but have a great impact on the quality of life of patients. Neuropsychiatric symptoms are commonly reported in CP, mostly chronic fatigue, cognitive disorders, attention disorders, among others. The pathophysiological mechanisms are not fully known, but the most described are hypoxia related neuronal damage, microvascular lesions, a persistent proinflammatory state, activation of latent viral infections, and alteration of the blood-brain barrier. There are no specific complementary tests to confirm the diagnosis of CP. There is also no specific treatment to date and most therapies are aimed at relieving symptoms and improving quality of life. This article provides a comprehensive bibliographic review of the most common neuropsychiatric manifestations of CP, including its probable pathophysiological mechanisms and the therapies proposed to date.